Political aspects of Neoprotestant organization missionary activity (Journal of Philosophy Culture and Political Science, 2018)
Revealing the article the concept of «missionary activity» is proved that this term appeared in Western Europein time of industry development and holding colonialist policy. There is given the classifi cation based on thepurposes and causes of missionary work.Socio-philosophical and religious study analysis has allowed to reveal, that missionary activity is one ofthe dynamic Protestant working methods, with a history spanning more than one year and more often it had theImperial character and caused protests from colonized countries. The conclusion is that Protestants distributeWestern civilization cultural achievements along with the religious traditions and the missionary activity is a toolexistential expansion.Key words: religion, politics, society, missionary activity, national interests